Fabrication of Upconverting Hybrid Nanoparticles for Near-Infrared Light Triggered Drug Release - Ranran Zhang; Risheng Yao; Binbin Ding; Yuxin Shen; Shengwen Shui; Lei Wang; Yu Li; Xianzhu Yang; Wei Tao (Advances in Materials Science and Engineering)
Low tissue penetration and harmful effects of (ultraviolet) UV or visible light on normal tissue limit exploiting nanocarriers for the application of light-controlled drug release. Two strategies may solve the problem: one is to improve the sensitivity of the nanocarriers to light to decrease the radiation time; the other one is using more friendly light as the trigger. In this work, we fabricated a core-shell hybrid nanoparticle with an upconverting nanoparticle (UCNP) as the core and thermo- and light-responsive block copolymers as the shell to combine the two strategies together. The results indicated that the sensitivity of the block copolymer to light could be enhanced by decreasing the photolabile moieties in the polymer, and the UCNP could transfer near-infrared (NIR) light, which is more friendly to tissue and cell, to UV light to trigger the phase conversion of the block polymers in situ. Using Nile Red (NR) as the model drug, the hybrid nanoparticles were further proved to be able to act as carriers with the character of NIR triggered drug release.